1992
DOI: 10.1063/1.463536
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of carbo-ions. VI. C–H stretching vibration of the acetylene ion C2H2+ and isotopic species

Abstract: The infrared spectra of the band of the 2Π–2Π asymmetric hydrogen stretching vibration in the three isotopic acetylene ions C2H2+ (ν3), 13C2H2+ (ν3), and DCCH+ (ν1) have been observed and analyzed. The high resolution infrared spectra were recorded using a difference-frequency laser spectrometer as the tunable coherent infrared source probing an ac glow discharge. Velocity modulation, noise subtraction, and unidirectional multipassing of the infrared beam through the discharge cell provided high sensitivity. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
40
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 75 publications
13
40
0
Order By: Relevance
“…Thus, excluding this line, our data were used as input to an asymmetric rotor model (Western 2016). Transitions from previous publications (Jagod et al 1992;Amano 2010;Gärtner et al 2013) were not included here as they did not significantly improve the ground state constants. The obtained rotational constants for the ground state of CH 2 D + are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, excluding this line, our data were used as input to an asymmetric rotor model (Western 2016). Transitions from previous publications (Jagod et al 1992;Amano 2010;Gärtner et al 2013) were not included here as they did not significantly improve the ground state constants. The obtained rotational constants for the ground state of CH 2 D + are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…This process is called laser induced reaction (LIR; Schlemmer et al 1999Schlemmer et al , 2002. For this vibrational excitation, a cw optical parametric oscillator (OPO) was held in resonance (within ±2 × 10 −4 cm −1 ) on selected transitions of the ν 1 or ν 4 bands (Jagod et al 1992;Gärtner et al 2013). With the IR frequency held on resonance, a cw (sub)mm-wave beam was shone simultaneously onto the trapped ion ensemble.…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic matrix element for the magnetic dipole operator in these cases is given by (Λ + g e Σ) × 0.009274 D. Thus, these transitions will be weak but potentially observable. (Jagod et al 1992;Kuhn et al 1986). A blackbody radiation temperature of 2.76 K has also been assumed in the calculation.…”
Section: Resultsmentioning
confidence: 99%
“…Notes. a Spectroscopic constants for H-C≡C-H + from Jagod et al (1992); estimated 1σ errors in line positions, based on the reported 1σ error in B 0 , are 3-12 MHz for the transitions listed, increasing as one moves to higher frequency transitions. b Spectroscopic constants for H-C≡C-C≡C-H + from Kuhn et al (1986); estimated 1σ errors in line positions are 5-50 MHz for the transitions listed.…”
Section: Resultsmentioning
confidence: 99%